Write Recount Text Learning Using a Genre-Based Approach in German Literature Class - Lutfi Saksono (IJORER : International Journal of Recent Educational Research, 2022)
Writing is a complex and challenging language skill because writing involves cognitive, affective, and creative elements. Rich vocabulary, understanding of grammatical features, and other aspects of writing also really determine someone's success in writing. Writing skills must be taught in foreign language learning because through writing skills, students can express emotions, thoughts, desires, and events with appropriate symbols. One approach that can help students improve their writing skills is the genre-based approach. Through this approach, students learn to write using specific text genres, such as recount text. Recount text is a type of text that tells the past. This study recounts text because students had just learned one of the past tenses in German, namely preterite. By using a genre-based approach in the study, it was found that students were able to 1) Improve their ability to identify characteristics and differences between several types of recount text; 2) Pay more attention to the text's structural elements and language style in the process of reading and writing; 3) Find essential information in the text according to the elements of the genre; 4) Increase self-confidence in writing.